Prospect of Sodium–Glucose Co-transporter 2 Inhibitors Combined With Insulin for the Treatment of Type 2 Diabetes - Yang, Yinqiu; Zhao, Chenhe; Ye, Yangli; Yu, Mingxiang; Qu, Xinhua (Frontiers in Endocrinology, 2020)
Sodium–glucose co-transporter 2 (SGLT2) inhibitors are a new family of antidiabetic drugs that reduce blood glucose independent of insulin. In this review, we present the advantages and adverse effects of SGLT2 inhibitors plus insulin therapy as a treatment regimen for patients with type 2 diabetes (T2D). Compared to placebo, SGLT2 inhibitors plus insulin therapy could significantly decrease fasting blood glucose and HbA1c, thereby reducing the daily required dose of insulin. A reduction in body weight and improvements in insulin resistance and β-cell function have also been widely reported with this therapy, and other potential advantages, including the reduction in blood pressure, adverse cardiovascular outcomes, and visceral adipose tissue volume, have been revealed. SGLT2 inhibitors cause a greater reduction than dipeptidyl peptidase-4 (DPP-4) inhibitors in body weight and the risk of cardiovascular disease. Furthermore, compared to glucagon-like-peptide-1 (GLP-1) agonists, SGLT2 inhibitors reduce blood pressure and heart failure. As this therapy is an oral preparation, an improvement in patient compliance is also achieved. Despite these advantages, however, combination therapy with SGLT2 inhibitors and insulin has several risks. Although no difference has been found in the incidence of hypoglycemic events and urinary tract infection between the administration of this combination and placebo, the risk of genital tract infections was reported to increase with the combination therapy. Additionally, bone adverse effects, euglycemic diabetic ketoacidosis, and volume depletion‑ and osmotic diuresis‑related adverse effects have been observed. Altogether, we could conclude that SGLT2 inhibitors plus insulin therapy is an efficient treatment option for patients with T2D, especially those requiring high daily insulin doses and those with insulin resistance, obesity, and a high risk of cardiovascular events. However, careful monitoring of the adverse effects of this combination is also warranted.